Response of wheat to winter night warming based on physiological and transcriptome analyses - Yonghui Fan; Yue Zhang; Yu Tang; Biao Xie; Wei He; Guoji Cui; Jinhao Yang; Wenjing Zhang; Shangyu Ma; Chuanxi Ma; Haipeng Zhang; Zhenglai Huang (Journal of Integrative Agriculture, 2025)
Global warming is primarily characterized by asymmetric temperature increases, with greater temperature rises in winter/spring and at night compared to summer/autumn and the daytime. We investigated the impact of winter night warming on the top expanded leaves of the spring wheat cultivar Yangmai 18 and the semi-winter wheat cultivar Yannong 19 during the 2020–2021 growing season. Results showed that the night-time mean temperature in the treatment group was 1.27°C higher than the ambient temperature, and winter night warming increased the yields of both wheat cultivars, the activities of sucrose synthase and sucrose phosphate synthase after anthesis, and the biosynthesis of sucrose and soluble sugars. Differentially expressed genes (DEGs) were identified using criteria of P-value<0.05 and fold change>2, and they were subjected to Gene Ontology (GO) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. Genes differentially expressed in wheat leaves treated with night warming were primarily associated with starch and sucrose metabolism, amino acid biosynthesis, carbon metabolism, plant hormone signal transduction, and amino sugar and nucleotide sugar metabolism. Comparisons between the groups identified 14 DEGs related to temperature. These results highlight the effects of winter night warming on wheat development from various perspectives. Our results provide new insights into the molecular mechanisms of the response of wheat to winter night warming and the candidate genes involved in this process.